2022
DOI: 10.1186/s12915-022-01289-0
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fixation by diverse diazotrophic communities can support population growth of arboreal ants

Abstract: Background Symbiotic ant-plant associations, in which ants live on plants, feed on plant-provided food, and protect host trees against threats, are ubiquitous across the tropics, with the Azteca-Cecropia associations being amongst the most widespread interactions in the Neotropics. Upon colonization of Cecropia’s hollow internodes, Azteca queens form small patches with plant parenchyma, which are then used as waste piles when the colony grows. Patches—found in many ant-plant mutualisms—are pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Second, Azteca workers deposit plant tissue, ant feces, and ant corpses onto patches and constantly shape and manipulate them [24,32,47,48]. Third, patch structures were found in almost every internode of the 93 colonies investigated, even in those with brood [48]. Last, none of the Azteca colonies inhabiting Cecropia stems from this study were found without patches in their nest.…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…Second, Azteca workers deposit plant tissue, ant feces, and ant corpses onto patches and constantly shape and manipulate them [24,32,47,48]. Third, patch structures were found in almost every internode of the 93 colonies investigated, even in those with brood [48]. Last, none of the Azteca colonies inhabiting Cecropia stems from this study were found without patches in their nest.…”
Section: Introductionmentioning
confidence: 63%
“…First, it was observed in 180 Cecropia saplings that the Azteca queens form the first patch before they start to lay their eggs [47]. Second, Azteca workers deposit plant tissue, ant feces, and ant corpses onto patches and constantly shape and manipulate them [24,32,47,48]. Third, patch structures were found in almost every internode of the 93 colonies investigated, even in those with brood [48].…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations